Improving the usability of interactive systems by incorporating design thinking into the engineering process: Raising computer science students' awareness of quality versus quantity in ideation - Sandnes, Frode Eika; Eika, Evelyn; Medola, Fausto Orsi [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Traditional engineering methods are considered unsuitable for the development of usable and engaging interactive systems such as online experimentation and simulation software. For systems involving users, user-centric design approaches are more appropriate. The ideation stage of design involves exploring the space of opportunities. One commonly held view in design disciplines is that quantity leads to quality. Yet, for related non-design disciplines such as engineering, quantity is often regarded as a negative characteristic associated with low quality. Focusing on quality alone may lead to inferior user experience and ineffective systems. This study describes an initiative to (1) collect empirical evidence to support the design-belief that quantity leads to quality and (2) to use the activity and its results as part of a pedagogical strategy to enhance students' awareness of the connections between quantity and quality during ideation. A class of 100 computer science students was divided into two groups. Both groups were given the same task to design a text-input strategy for individuals with motor disabilities but with different focuses: one group was asked to focus on quality of ideas and the other group on the quantity of ideas. The results show that the students who focused on quantity of ideas produced better quality concepts compared to the students that focused on quality. The results were presented to and discussed with the students as a part of the learning process.
Keywords: human computer interaction; ideation; motor disability; sketching; text entry; universal design education